Pengaruh Influencer Review, Brand Love, dan E-Wom Terhadap Keputusan Pembelian Produk Kosmetik Implora Melalui Kualitas Produk Sebagai Variabel Intervening pada Followers Instagram Imploracosmetics - Devi Pratiwi; Novi Sri Wiarti; Fitrianingsih; Bobby Hartanto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the influence of Influencer Reviews, Brand Love, and E-Wom on Purchasing Decisions for Implora Cosmetics Products through Product Quality as an Intervening Variable on Imploracosmetics Instagram Followers. The research method used is a quantitative method using the help of Smart PLS version 3.0 which was collected from the results of distributing questionnaires to 100 Imploracosmetics Instagram Followers. The analytical method used in this research is to use instrument tests, namely validity and reliability tests. measurement model (outer model), namely the validity test, reliability test, then the structural model (inner model) including: coefficient of determination/r-square (r2), goodness of fit model and hypothesis testing with the t-statistic test and indirect influence test (indirect effect). The results of Smart PLS 3.0 in this research are that influencer reviews have an influence on product quality but have no influence on purchasing decisions, the brand love variable has no influence on purchasing decisions and product quality. E-Wom influences product quality and purchasing decisions. Product quality influences purchasing decisions. Influencer reviews influence purchasing decisions with product quality as an intervening variable, Brand love has no influence on purchasing decisions with product quality as an intervening variable, and E-Wom influences purchasing decisions with product quality as an intervening variable